If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = s + -12 Reorder the terms: 18 = -12 + s Solving 18 = -12 + s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-1s' to each side of the equation. 18 + -1s = -12 + s + -1s Combine like terms: s + -1s = 0 18 + -1s = -12 + 0 18 + -1s = -12 Add '-18' to each side of the equation. 18 + -18 + -1s = -12 + -18 Combine like terms: 18 + -18 = 0 0 + -1s = -12 + -18 -1s = -12 + -18 Combine like terms: -12 + -18 = -30 -1s = -30 Divide each side by '-1'. s = 30 Simplifying s = 30
| -5+7d+3=33+2d | | y-14=(x-4) | | 2(x+9)=2 | | 9/-1 | | 4-9x-3x=32 | | 4x+5x=ax^2 | | x+8=-16 | | 6x+14-2x=54 | | 6(2s-t)= | | 2/3n-5/12=21/4 | | 5x(2x+6)= | | (1-7N)(5)= | | 2x(x-6)(3x-9)=0 | | b+9-2b=16+6b | | 0.5(x-12)=9 | | 6n+4-3n-3= | | 2x(x-6)(x-9)=0 | | b/7=21 | | 2b+3b-5= | | 6x+21=14x-4 | | 5/3-2x=-8/3 | | 6x+2=14x-4 | | 7/b=21 | | Y=2.6x-9 | | 8(x-1)=-(x+19) | | (4x^3)-(3x^2)-16x=0 | | 4.6(2y+3)=3.7y-.4 | | 7=21b | | (4x^3)-(3x^2)-16x-1=0 | | x/2.7+3.6=4.8 | | (4x^3)-(3x^2)-16x-1=02 | | 2400/6y |